Daily mean surface meteorology and river discharge in Central Sulawesi for the period 2002-2005 - Constanze Leemhuis (PANGAEA, 2007)
The El Niño/ Southern Oscillation (ENSO) phenomenon is the strongest known natural interannual climate fluctuation. The most recent two extreme ENSO events of 1982/83 and 1997/98 severley hit the socio-economy of main parts of Indonesia. As the climate variability is not homogeneous over the whole Archipelago of Indonesia, ENSO events cause negative precipitation anomalies of diverse magnitude and uration in different regions. Understanding the hydrology of humid tropical catchments is an essential prerequisite to investigate the impact of climate variability on the catchment hydrology. Together with the quantitative assessment of future water resource changes they are essential tools to develop mitigation strategies on a catchment scale. These results can be integrated into long term Integrated Water Resource Management (IWRM) strategies. The general objective of this study is to investigate and quantify the impact of ENSO caused climate variability on the water balance and the implications for water resources of a mesoscale tropical catchment.
Supplement to: Leemhuis, C (2006): The Impact of El Niño Southern Oscillation Events on Water Resource Availability in Central Sulawesi, Indonesia: A hydrological modelling approach [dissertation]. Georg-August-Universität zu Göttingen, Germany, 172 pp, hdl:11858/00-1735-0000-0006-B326-B